MODEL DINAMIK PERTUMBUHAN PENDUDUK DAN KUALITAS LINGKUNGAN DI KOTA PADANG - Indang Dewata (Jurnal Kependudukan dan Pembangunan Lingkungan, 2020)
High population growth is a major problem in many developing countries. High population growth has an impact on environmental quality. The purpose of this study describes the dynamic modeling and impact of population growth on environmental quality in Padang City. The method used in dynamic modeling is system approach using powersim 10 software. The population growth in Padang City of the period of 2000-2016 is about 1.3 percent / year, and it is estimated that by 2050 the population will increase to 951.071 inhabitants. The amount of waste produced every year is 2,376 tons / year, and will increase by 2050 to 2,378 tons / year. Therefore, it is necessary for the role of government in controlling population growth and improving the quality of the environmen